The assassination of Herbert Chitepo : texts and politics in Zimbabwe - White, Luise (Indiana University Press ; Double Storey Books, 2003)
On 18 March 1975, Herbert Chitepo, an African nationalist in exile and chairman of the war council that struggled to liberate Zimbabwe from white-ruled Rhodesia, was filled by a car bomb. Since then, there have been four confessions and at least as many accusations about who was responsible. In The Assassination of Herbert Chitepo, Luise White does not set out to resolve questions about who was accountable for this horrible murder. Instead, in a style that is as much murder mystery as it is history writing, she uncovers what is at stake in the various confessions and why Chitepo's assassin.